Ranking different types of tourist accommodation facilities in Serbia using PROMETHEE-GAIA method - Ilić, Ivana (Hotel and Tourism Management, 2017)
This paper presents the ranking of different types of tourist accommodation facilities in Serbia with the highest number of arrivals and overnight stays concerning both domestic and foreign tourists in 2015. PROMETHEE-GAIA method is used for the ranking, with respect to two scenarios (Scenario 1 – ranking different types of tourist accommodation facilities with the highest number of arrivals and Scenario 2 – ranking different types of tourist accommodation facilities with the highest number of overnight stays). Data used in this analysis are taken from the Statistical Yearbook of the Republic of Serbia 2016. Domestic and foreign tourists at the north and the south of the country are taken as criteria, and 16 types of tourist accommodation facilities in Serbia are defined as alternatives. This way of multicriteria ranking of the most visited types of tourist accommodation, obtained by PROMETHEE-GAIA method, could be considered as contribution to methodology that can be used in the analysis of tourism potentials. The analysis results of both scenarios show that the best ranked are hotels while the worst ranked are hunting houses and cottages and boarding houses.